OUTSOURCING STRATEGY AND ORGANIZATIONAL PERFORMANCE: EMPIRICAL EVIDENCE FROM NIGERIA MANUFACTURING SECTOR - ‘Supo Akewushola; Wale Elegbede (European Scientific Journal, ESJ, 2013)
Globalization of practices driven by accelerated competition among manufacturing and service delivery organizations has pushed firms to create value for money through efficient use of limited resources. Outsourcing is one of the management tools that are gaining currency among managers in addressing the new dynamic business order. This study examined the axiomatic relationship between outsourcing strategy and organizational performance in Nigeria manufacturing sector. The study adopted a stratified sampling technique to arrive at 120 sample elements for the study. Some of the top and middle level managers of Cadbury Nigeria Plc and Nestle Foods Plc were interviewed to further elicit information on the key variables. Copies of the questionnaire were administered and the data obtained were analyzed using Regression analysis. The questionnaire for this study was subjected to test- re-test reliability assessment. Opinions and observations of experts and professionals were incorporated into scale questions in order to ensure the content validity. The findings reveal that firms that outsource experience reduce average cost, increased sales turnover and profitability, enhance expertise, improve service quality, reduce staff strength, streamline the production process, reduced administrative burden and save time for core activities. It was recommended that companies that outsource should continue to monitor the contractor’s activities in order to ensure compliance with best practices. Workers should be made to embrace the strategy before implementation so as to alley the fear of loss of Jobs.